2015
DOI: 10.1136/bcr-2014-208677
|View full text |Cite
|
Sign up to set email alerts
|

A middle-aged man presenting with unexplained mucosal erosions and progressive dyspnoea

Abstract: Paraneoplastic pemphigus (PNP) is a rare syndrome driven by antibodies (IgG) binding to desmogleins and other epidermal proteins leading to skin erosions. In rare instances, these same IgG proteins may also target the bronchial mucosa leading to an irreversible fibrotic reaction within the epithelium and subsequent obstructive lung disease. A 51-year-old man presented to the emergency department with 2–3-month history of dyspnoea as well as oral and genital ulcerations and inguinal lymphadenopathy. The ulcerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 7 publications
(13 reference statements)
0
18
0
Order By: Relevance
“…The mechanism of how PNP and CD cause BO has not been completely elucidated. Previous studies have shown that CD8+ T lymphocytes mediate cytotoxic immunity, IgG autoantibody deposition, and acantholysis, which further induces airway inflammation, with subsequent irreversible fibrotic change . In a previous study in China, BO was reported in 10 of 37 patients with PNP and CD (27%) .…”
Section: Discussionmentioning
confidence: 92%
“…The mechanism of how PNP and CD cause BO has not been completely elucidated. Previous studies have shown that CD8+ T lymphocytes mediate cytotoxic immunity, IgG autoantibody deposition, and acantholysis, which further induces airway inflammation, with subsequent irreversible fibrotic change . In a previous study in China, BO was reported in 10 of 37 patients with PNP and CD (27%) .…”
Section: Discussionmentioning
confidence: 92%
“…Ulceration may involve the entire oral mucosal surfaces and may represent the sole manifestation of this condition. A painful stomatitis is also commonly shown caused by massive erosion in the oropharynx [ 2 , 21 , 53 , 55 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Lesions can also affect regions such as the oropharynx, esophagus, stomach, duodenum, large intestine, conjunctiva, and anogenital region [2,3,7,39,41,44,45]. The involvement of the oropharynx and esophagus commonly triggers painful sensations and dysphagia [4].…”
Section: Secondary Mucosal Lesionsmentioning
confidence: 99%
“…The use of otorhinolaryngological examination is very important to differentiate the diseases that affect the mucous membranes. Well-done physical examination of the oral cavity, histopathological analysis characteristics, cutaneous involvement, and the presence of IIF strongly suggest for the diagnosis of PNP [40,44,67].…”
Section: Differential Diagnosismentioning
confidence: 99%